2018
DOI: 10.1186/s41044-018-0032-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of disease-distinct complex biomarker patterns by means of unsupervised machine-learning using an interactive R toolbox (Umatrix)

Abstract: Background: Unsupervised machine-learned analysis of cluster structures, applied using the emergent self-organizing feature maps (ESOM) combined with the unified distance matrix (U-matrix) has been shown to provide an unbiased method to identify true clusters. It outperforms classical hierarchical clustering algorithms that carry a considerable tendency to produce erroneous results. To facilitate the application of the ESOM/U-matrix method in biomedical research, we introduce the interactive R-based bioinforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 59 publications
2
44
0
Order By: Relevance
“…Valleys indicate clusters of functionally similar genes based on the significant GO term annotations. The figure was created using the R software package (version 3.3.2 for Linux; http://CRAN.R-project.org/; R Development Core Team, ) using our R library ‘Umatrix’ ( https://cran.r-project.org/package=Umatrix; Lötsch et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Valleys indicate clusters of functionally similar genes based on the significant GO term annotations. The figure was created using the R software package (version 3.3.2 for Linux; http://CRAN.R-project.org/; R Development Core Team, ) using our R library ‘Umatrix’ ( https://cran.r-project.org/package=Umatrix; Lötsch et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…The ‘map’ was further enhanced by calculating a so‐called P‐matrix (Ultsch, ), which displays the probability of a data point as pfalse(xfalse)={datapointsxidfalse(xi,xfalse)<=r} estimated as the number of data points in a sphere with radius r around x at each grid point on the ESOM's output grid. The calculations were performed using our R library ‘Umatrix’ (https://cran.r-project.org/package=Umatrix; Lötsch et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…When analyzing the same data using emergent self-organizing feature maps (ESOM), projecting the data on a grid of thousands of artificial neurons [7] and combining it with U-matrix methods [4,5], it was correctly concluded that there is no group structure in these data. As shown in the lower-left panel of Figure 1, the U-matrix consists of a random structure without subgroups.…”
Section: Results Of T-sne Analysis In Artificial Data Setsmentioning
confidence: 99%
“…Results of an alternative projection and subgroup detection technique, implemented as ESOM/U-matrix, which clearly indicate the absence of any systematic data structures, are shown at lower-left panel. The figure has been created based on the t-SNE analysis implemented in the R library "tsne" [3] and the U-matrix was obtained using the R library "Umatrix" [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation